2022
DOI: 10.1126/sciadv.abn7983
|View full text |Cite
|
Sign up to set email alerts
|

EGFR is a master switch between immunosuppressive and immunoactive tumor microenvironment in inflammatory breast cancer

Abstract: Inflammatory breast cancer (IBC), the most aggressive breast cancer subtype, is driven by an immunosuppressive tumor microenvironment (TME). Current treatments for IBC have limited efficacy. In a clinical trial (NCT01036087), an anti-EGFR antibody combined with neoadjuvant chemotherapy produced the highest pathological complete response rate ever reported in patients with IBC having triple-negative receptor status. We determined the molecular and immunological mechanisms behind this superior clinical outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 91 publications
1
12
0
Order By: Relevance
“…However, our data about the immunosuppressive function for MFGE8 are in line with others, where MFGE8 expression in esophageal cancer was found to correlate with decreased CD8 + T cell infiltration, and MFGE8 impaired T cell activation in the context of transplantation ( 83 ). Furthermore, a recent study demonstrated a critical role for EGFR in creating an immunosuppressive environment in breast cancer ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our data about the immunosuppressive function for MFGE8 are in line with others, where MFGE8 expression in esophageal cancer was found to correlate with decreased CD8 + T cell infiltration, and MFGE8 impaired T cell activation in the context of transplantation ( 83 ). Furthermore, a recent study demonstrated a critical role for EGFR in creating an immunosuppressive environment in breast cancer ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…An ongoing clinical trial (NCT05177796) is evaluating the enhancement of immunotherapy by targeting the EGFR pathway with panitumumab and pembrolizumab in combination with neoadjuvant chemotherapy in TN-IBC. In a humanized mouse model study, panitumumab remodeled the IBC tumor microenvironment (TME) by increasing cytotoxic T cells and reducing immunosuppressive regulatory T cells and M2 macrophages [ 38 ]. Furthermore, panitumumab reduced the gene expression of immunosuppressive cytokines, including TGFB1, TGFB2, TGFB3, CCL2, and IL1B [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a humanized mouse model study, panitumumab remodeled the IBC tumor microenvironment (TME) by increasing cytotoxic T cells and reducing immunosuppressive regulatory T cells and M2 macrophages [ 38 ]. Furthermore, panitumumab reduced the gene expression of immunosuppressive cytokines, including TGFB1, TGFB2, TGFB3, CCL2, and IL1B [ 38 ]. EGFR targeted therapy has been shown to modulate the TME in lung cancer [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, M2 macrophages exhibit potent anti-inflammatory activity, countering the pro-inflammatory response of M1 by upregulating IL-10 and downregulating IL-12 with markers including CD206, CD163 and CD68 (74). Previously, it was reported that macrophage M2 polarization is generated by the tumor microenvironment, and then polarized M2 macrophages promote tumor cell proliferation, invasion, and EMT (75)(76)(77). Researchers found that hypoxia induced tumor-associated macrophage enrichment and M2 polarization via HIF.…”
Section: Role Of Exosomes In the Tme Of Nsclcmentioning
confidence: 99%